Aprender brincando em língua estrangeira: uma perspectiva dos multiletramentos na educação infantil - Silva, Samanta Malta Pereira da (2015)
This research aims at investigating whether and how the work with Multiliteracies through Social Activities in English provides opportunities to children of an Educational Center in the central area of São Paulo build new ways of acting in the world. In order to achieve this goal, this research relies on the Pedagogy of Multileracies, which is based on the variability of meaning conventions present in various contexts of cultural and social representation, multimodality and multimedia. It is also supported by the curricular organization based on Social Activities (LIBERALI, 2009) which, in turn, is based on the Activity Theory a socio historical and cultural approach (VYGOTSKY, 1930/1934; LEONTIEV, 1977; ENGESTRÖM, 1987). This study also works with the conception of language as constitutive in building diverse knowledge, enabling individuals to experience different ways of knowing and living in a different language. This is a Critical Collaborative Research - PCCol (Magalhães, 2002, 2004, 2007), based on the theoretical and methodological framework and supported by collaboration categories and contradiction, introduced by Marx (1845) and discussed by Vygotsky (1934), which allows analysis and understanding of discourses by many perspectives and the transformation of the context through the creation of new action guidelines. This study was developed with children from two to four years old in a Children's Educational Center located near the downtown area. The production of data was conducted through multimodal transcription of video-recorded classes during one year and a half. Lesson planning documents and the corresponding classes were analyzed according to the dialogic-enunciative-multimodal perspective. Results show that the high level of engagement of the children in the Social Activities and the use of a variety of media and modes collaborated in the production process of new knowledge by the children